2019
DOI: 10.1002/phar.2200
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Clostridium difficile Infection in Critically Ill Adults

Abstract: The incidence and severity of Clostridium difficile infection (CDI) remain high across intensive care units in the United States despite national efforts to decrease this escalating health care burden. Most published literature and guidelines address treatment rather than prevention, yet this approach may be too downstream to limit morbidity and mortality from the disease and its complications. Mechanisms to prevent CDI successfully include reducing modifiable risk factors and minimizing horizontal transmissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 69 publications
(164 reference statements)
0
6
0
Order By: Relevance
“…This study emphasizes the challenging and common clinical question that arises when patients with a recent or persistent history of CDI require subsequent antibiotics, as there is little data to guide clinical practice regarding the provision of secondary prophylaxis, and many unanswered questions remain. 4,14 To our knowledge, based on an extensive literature search and a review of information from clinicaltrials. gov, ours is the first known study to evaluate the role of secondary CDI prophylaxis in a critically ill patient population, and there are no ongoing trials evaluating CDI secondary prophylaxis specifically in the ICU setting.…”
Section: Discussionmentioning
confidence: 99%
“…This study emphasizes the challenging and common clinical question that arises when patients with a recent or persistent history of CDI require subsequent antibiotics, as there is little data to guide clinical practice regarding the provision of secondary prophylaxis, and many unanswered questions remain. 4,14 To our knowledge, based on an extensive literature search and a review of information from clinicaltrials. gov, ours is the first known study to evaluate the role of secondary CDI prophylaxis in a critically ill patient population, and there are no ongoing trials evaluating CDI secondary prophylaxis specifically in the ICU setting.…”
Section: Discussionmentioning
confidence: 99%
“…A metaanalysis 6 indicated that the benefit of acid suppressants for stress ulcer prophylaxis is limited to prevention of gastrointestinal bleeding, but mortality is not changed. Moreover, two other studies 7,8 suggested that acid suppressants may be associated with multidrug-resistant pneumonia and Clostridium difficile infection, respectively. The latter 8 provides actionable interventions to reduce C. difficile infection that include minimizing acid suppressant therapy.…”
Section: E D I T O R I a Lmentioning
confidence: 99%
“…Moreover, two other studies suggested that acid suppressants may be associated with multidrug‐resistant pneumonia and Clostridium difficile infection, respectively. The latter provides actionable interventions to reduce C. difficile infection that include minimizing acid suppressant therapy. At the very least, the sentiment expressed in these three articles leads to questions surrounding which outcome is important to prevent (gastrointestinal bleeding vs mortality) relative to the risk of increasing complications that may lead to worse outcomes.…”
mentioning
confidence: 99%
“…Robust hygiene strategies (in particular a strong hand hygiene program), diagnostic and antimicrobial stewardship, and particular prophylaxis maneuvers such as continuation of oral vancomycin or fidaxomicin alongside systemic antibiotics have all demonstrated benefit. It is of fundamental importance to isolate infected patients as soon as possible after the onset of their first symptoms [85][86][87]. Many randomized controlled trial studies assessed probiotics as an adjunct to standard antibiotic treatment for the prevention of C. difficile infection.…”
Section: Hais Preventionmentioning
confidence: 99%